Mapping scientific research on sports economics: A scientometric study of hotspots and emerging trends - Zhang, B.; Yu, W. (Journal of Sports Analytics, 2025)
This scientometric study maps the research hotspots and emerging trends in sports economics research through a comprehensive analysis of 6553 Web of Science articles (2005-2025) using advanced bibliometric tools of CiteSpace and VOSviewer. In contrast to narrative reviews, this study combines co-citation clustering, keyword burst detection, and multi-level collaboration network analyses to reveal the field's evolution. Results indicate sustained growth in annual publications, dominated by the U.S. and China, with pivotal contributions from institutions such as the German Sport University Cologne and leading authors including Wicker and Humphreys, who have been instrumental in shaping global collaborative networks. Co-citation analysis identifies seven key research hotspots: regional economic effects of sports tourism, public policy efficacy, brand commercialization, socioeconomic contributions, digital innovation, sustainable development, and globalization. Four emerging trends are highlighted via keyword burst detection: gender pay gaps, media's economic role in brand value, public health linkages, and satisfaction dynamics. This study provides a data-driven framework for optimizing event-driven growth, addressing inequities, and leveraging innovations for socioeconomic resilience.